2017
DOI: 10.31138/mjr.28.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Lupus thrombocytopenia: pathogenesis and therapeutic implications

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License. Systemic Lupus Erythematosus (SLE) is a systemic autoimmune disorder that is frequently complicated by hematological manifestations such as hemolytic anemia, leukopenia and thrombocytopenia. 1,2 These disorders are included in the diagnostic criteria of SLE both in the earlier (1982), as well as in the revised criteria of the American College of Rheumatology (2003), and the 2012 Systemic Lupus International Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…In a case series of patients admitted to an intensive care unit (ICU) in Wuhan, a platelet count of <100,000/μL was observed in only 5% of patients [29]. Thrombocytopenia <100,000/μL has been reported in 20% to 40% of patients with SLE [30]. In the present series, thrombocytopenia was reported in 6 of 7 patients and was considered severe (<50,000/μL) and refractory to treatment in 5 cases.…”
Section: Discussionmentioning
confidence: 43%
“…In a case series of patients admitted to an intensive care unit (ICU) in Wuhan, a platelet count of <100,000/μL was observed in only 5% of patients [29]. Thrombocytopenia <100,000/μL has been reported in 20% to 40% of patients with SLE [30]. In the present series, thrombocytopenia was reported in 6 of 7 patients and was considered severe (<50,000/μL) and refractory to treatment in 5 cases.…”
Section: Discussionmentioning
confidence: 43%
“…In a case series of patients admitted to an intensive care unit (ICU) in Wuhan, a platelet count of < 100,000/μL was observed in only 5% of patients [29]. Thrombocytopenia < 100,000/μL has been reported in 20-40% of patients with SLE [30]. In the present series, thrombocytopenia was reported in 6 of 7 patients and was considered severe (< 50,000/μL) and refractory to treatment in 5 cases.…”
Section: Discussionmentioning
confidence: 99%
“…It may be the initial feature of lupus in 16% of patients, presenting months or maybe 10 years before diagnosis. Many studies have found that thrombocytopenia is associated with higher mortality, although the onset and severity have not been clearly defined [19]. Treatment options are similar to idiopathic thrombocytopenic purpura, i.e.…”
Section: Discussionmentioning
confidence: 99%